Simultaneous Determination of Catechol and Paraquat Using a Flexible Electrode of PBAT and Graphite Modified with Gold Nanoparticles and Copper Phthalocyanine (g-PBAT/AuNP/CuTsPc) LbL Film - MacIel, Cristiane C. [UNESP]; Freitas, Amanda De S. M.; Medrades, Jennifer P.; Ferreira, Marystela [UNESP] (The Electrochemical Society, 2022)
A flexible sensor based on polymer poly (butylene adipate-co-terephthalate) (PBAT) mixed with graphite was surface modified with AuNP (gold nanoparticule) and copper phthalocyanine using Layer-by-Layer (LbL) technique for simultaneous determination of catechol (CC) and paraquat (PQ). The device with and without modification was characterized by contact angle, Scanning Electron Microscopy (SEM), and Fourier Transform Infrared Spectroscopy (FTIR). Electrochemical characterization was performed by Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS). Differential Pulse Voltammetry (DPV) technique was used to detect CC and PQ molecules in an interval of 100 to 200 μM, some parameters were obtained from the analytical curve, such as linear regression values (R2) equal to 0.9998 and 0.9993 and detection limit (LOD) equal to 1.36 × 10-6 and 1.31 × 10-6 for CC and PQ, respectively. The sensor (g-PBAT/AuNP-PAH/CuTsPc)3 presented good stability, reproducibility, and repeatability, with recovery values ranging between 98.4%-105.6% for CC and 94.4%-106.1% for PQ when the sensor was subjected to analysis of samples contaminated with tap water. Electrodes produced in this work had the advantage of being flexible, disposable, reproducible, and of low manufacturing cost, which makes them attractive for portable environmental analysis.